المشتقات ودلالاتها في شعر عبد الله البردوني – دراسة في نماذج مختارة - هدى بعارة (My University, 2023)
Abstract This research, titled “Derivatives and Their Significance in the Poetry of Abdullah Al-Bardouni,” aims to study the morphological semantics of selected models from the collection of the poet Abdullah Al-Bardouni, with the aim of standing at the structure of the derivatives in them and their significance, and investigating the aesthetic aspects in them. What is meant by derivatives is the group of names that are formulated From the verb (or the infinitive), the most famous of which are: the subject noun, the participle noun, the exaggerated form, the suspicious adjective, the noun of preference, the noun of the instrument, the nouns of place and time. The research came with a plan that started with an introduction, which dealt with the general framework of the study in terms of the problem at hand, the objectives, the reasons for choosing the topic, and the classification of the research, and this was followed by the first chapter in which we dealt with theoretical concepts, while the chapter came with an applied character where we tried to track the derivatives and their implications in the blog, And we concluded the research with a conclusion, in which we mentioned the total results reached. ---------------- الملخّص يروم هذا البحث الموسوم ب "المشتقّات ودلالتها في شعر عبد الله البردوني –دراسة في نماذج مختارة-" إلى دراسة صرفيّة دلاليّة لنماذج مختارة من ديوان الشّاعر عبد الله البردوني، وذلك بهدف الوقوف عند بنية المشتقات فيها ودلالتها وتقصّي مواطن الجماليّة فيها. والمقصود بالمشتقات هي مجموعة الأسماء الّتي تتمّ صياغتها من الفعل ( أو المصدر)، وأشهرها: اسم الفاعل، اسم المفعول، صيغة المبالغة، الصّفة المشبّهة، اسم التّفضيل، اسم الآلة، اسما المكان والزّمان. وجاء البحث بخطّة استهلّت بمقدّمة والّتي تناولنا فيها الإطار العام للدّراسة من ناحية الإشكاليّة المطروحة، والأهداف، وأسباب اختيار الموضوع، وتبويب البحث، وأتبعنا ذلك بالفصل الأوّل الّذي تناولنا فيه المفاهيم النّظرية، في حين جاء الفصل بصبغة تطبيقيّة أين حاولنا تتبع المشتقّات ودلالاتها في المدوّنة، وختمنا البحث بخاتمة أوردنا فيها جملة النّتائج المتوصّل إليها. ----------------- Résumé Cette recherche, intitulée "Les dérivés et leur signification dans la poésie d'Abdullah Al-Bardouni", vise à étudier la sémantique morphologique de modèles sélectionnés de la collection du poète Abdallah Al-Bardouni, dans le but de se tenir à la structure des dérivés. en eux et leur signification, et en enquêtant sur les aspects esthétiques en eux. le nom participe, la forme exagérée, l'adjectif suspect, le nom de préférence, le nom de l'instrument, les noms de lieu et de temps. La recherche s'accompagnait d'un plan qui commençait par une introduction, qui traitait du cadre général de l'étude en termes de problème posé, des objectifs, des raisons du choix du sujet, et de la classification de la recherche, et ce a été suivi du premier chapitre dans lequel nous avons traité des concepts théoriques, tandis que le chapitre est venu avec un caractère appliqué où nous avons essayé de suivre les dérivés et leurs implications dans le blog, Et nous avons conclu la recherche par une conclusion, dans laquelle nous avons mentionné le résultats totaux atteints.